SHARIA DISCLOSURE AND MARKET VALUE: STUDY OF LIST OF SHARIA EFFECT (DES) IN INDONESIA - Ahmad Dzakiyuddin; Bambang Sutopo (International Journal of Accounting, Finance and Business, 2020)
This study aims to determine the relationship between sharia disclosure and market value in companies included in the list of sharia securities in Indonesia. Market value is proxied by the ratio of tobin’s q. Sharia disclosure is measured by financial services authority (POJK) regulations regarding 3 criteria for issuance of sharia securities list in accordance with sharia principles, leverage ratios and revenue recognition ratios. The Islamic governance score is a proxy for the characteristics of the sharia supervisory board (DPS). The sample in this study were companies that were included in the sharia securities list category in 2018. The number of samples used was 352 companies taken through purposive sampling. The analytical method of this study uses multiple linear regression. The results of this study indicate that the disclosure of sharia has a significant positive relationship with market value; conformity with sharia principles, revenue recognition ratios and Islamic governance scores have a positive and insignificant relationship with market values; conversely the leverage ratio has no relationship and is not significant to market value.